Exploring the Use and Cultural Significance of Bimanese Idioms in Social Interactions: Case Study at LDK AL Muhajirin at STKIP Taman Siswa Bima - Ramli; Irma, Ade (The Indonesian Institute of Science and Technology Research, 2024)
This research investigates the use and types of Bimanese idioms within the social interactions of LDK AL Muhajirin at STKIP Taman Siswa Bima. Employing a descriptive qualitative methodology, the study examines four recorded interactions and 3 study sessions, revealing 26 instances where Bimanese idioms were utilized. These idiomatic expressions were associated with various pragmatic speech acts, including illocutionary, elocutionary, and perlocutionary acts, involving 17 speakers and 41 listeners. Furthermore, the research categorizes these idioms into distinct types, emphasizing their cultural significance.